Еволюція образу провінції в австрійській літературі XX ст. - Isapchuk, Yulia (Wydawnictwo Uniwersytetu w Białymstoku, 2022)
The study analyses three formation phases of the Austrian literature in the20th century, which relate to the explanation of the depiction’s principles of the province. The role of the literary tradition in the understanding of the native region’s chronotope is emphasized. The attention is drawn to the change in the connotation of the Austrian regional literature (Heimatliteratur) in the context of historical, social, and aesthetic factors with the parallel modification of the region’s image: the allGerman antimodernist movement Heimatkunst and its Austrian version Provinzkunst; radicalization of the interwar period and the “Blood and Soil Literature” (Blut-und-Boden-Literatur); updating by the new movement “Anti-regional literature” (AntiHeimatliteratur). The evolution of the reception and interpretation of the province’s image as a fabula’s constant of the text is studied, including the transmission from idealization to the desacralization of the locus.
Keywords: province, region, Heimatkunst, Provinzkunst, regional literature (Heimatliteratur), antiregional literature (Antiheimatliteratur/AntiHeimatliteratur), Austrian literature of the 20th century